Информационно-образовательное пространство вуза как фактор развития субъектности будущего учителя - Смаглий, Т.И. (My University, 2013)
The article deals withthe concept and structureof information andeducational environmentof the university.Defined by itsopportunities in the developmentof subjectivityfuture teachers.Special attentionis paid tothe pedagogicalcomponentof information-educational environment of the university.